Pengaruh Kepercayaan, Kemudahan, dan Kualitas Informasi Terhadap Keputusan Pembelian Produk Fashion Islami Melalui Shopee dalam Perspektif Ekonomi Islam - Sania Layaliyal; Sania Layaliyal Ifadhoh; Susilo, Edi (Efektor, 2025)
This study aims to examine the effect of trust, convenience, and information quality on shopping decisions for Islamic fashion products through shopee from an Islamic economic perspective in Central Java province. This research uses a mix method, which is a combination of quantitative and qualitative methods. Quantitative sent questionnaires to 100 selected respondents using non-statistical sampling techniques through purposive sampling. Data analysis was conducted using SmartPLS 4.0. Qualitative was conducted with 10 informants from various backgrounds (5 students, 1 teacher, 1 private employee, 2 students, 1 housewife), who are also active Shopee users and have purchased Islamic fashion more than twice. The findings show that trust has no influence on the decision to buy Islamic fashion through shopee from an Islamic economic point of view. Meanwhile, ease of Us and information quality have an influence on purchasing decisions for Islamic fashion products through shopee in an Islamic economic perspective.